EVALUASI ASPEK KENYAMANAN PENCAHAYAAN SEKOLAH LUAR BIASA (SLB) HELEN KELLER INDONESIA - Christian, Ivan; Octarino, Christian N. (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
Lighting is one of the important aspects needed to support people daily activities, including for teaching and learning activities in school. Helen Keller School Indonesia is one of the special schools that accommodate children with special needs, especially the blind and deaf. In this school most of the students are low visioners or weak vision, which is one type of blind. Lighting is an important aspect, considering low visioners are not completely blind, so that with some tools and good lighting conditions they can still doing their activities. This study aims to evaluate the existing lighting levels in Helen Keller School building, whether it meets the standards for educational buildings. The method used is direct measurement in the field using lux-meter, then doing a comparison analysis between field results with standards. The evaluation results will be used as a basis for design recommendations that will optimize not only artificial lighting, but also natural lighting to support energy savings in sustainable development.